Molecular cloning of the gene promoter encoding the human CaVγ2/Stargazin divergent transcript (CACNG2-DT): characterization and regulation by the cAMP-PKA/CREB signaling pathway - Muñoz-Herrera, David; Calderón-Rivera, Aida; Zarco, Natanael; Corzo-Lopez, Alejandra; Leyva-Leyva, Margarita; Monjaraz, Eduardo; Sandoval, Alejandro; Oviedo, Norma; González-Ramírez, Ricardo; Felix, Ricardo (Frontiers in Physiology, 2023)
CaVγ2 (Stargazin or TARPγ2) is a protein expressed in various types of neurons whose function was initially associated with a decrease in the functional expression of voltage-gated presynaptic Ca 2+ channels (CaV) and which is now known to promote the trafficking of the postsynaptic α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptors (AMPAR) towards the cell membrane. Alterations in CaVγ2 expression has been associated with several neurological disorders, such as absence epilepsy. However, its regulation at the transcriptional level has not been intensively addressed. It has been reported that the promoter of the Cacng2 gene, encoding the rat CaVγ2, is bidirectional and regulates the transcription of a long non-coding RNA (lncRNA) in the antisense direction. Here, we investigate the proximal promoter region of the human CACNG2 gene in the antisense direction and show that this region includes two functional cAMP response elements that regulate the expression of a lncRNA called CACNG2-DT. The activity of these sites is significantly enhanced by forskolin, an adenylate cyclase activator, and inhibited by H89, a protein kinase A (PKA) antagonist. Therefore, this regulatory mechanism implies the activation of G protein-coupled receptors and downstream phosphorylation. Interestingly, we also found that the expression of CACNG2-DT may increase the levels of the CaVγ2 subunit. Together, these data provide novel information on the organization of the human CACNG2-DT gene promoter, describe modulatory domains and mechanisms that can mediate various regulatory inputs, and provide initial information on the molecular mechanisms that regulate the functional expression of the CaVγ2 protein.